Genetic Algorithm Approach to Logistics Transportation and Distribution Problems: A Case Study of Parcel Delivery Services - Miftahol Arifin (OPSI, 2021)
Transportation and distribution activities require companies to have careful transportation planning to maintain resource efficiency. One form of planning in the transportation is planning the route and the number of vehicles. The research output is to get the best shipping route from each transportation in the form of the smallest shipping cost, delivery distance and shortest time. The approach used to determine the best route is the genetic algorithm (GA) method. In the application of GA in finding routes according to the objective, it gives the best results. From the results of the study, it was concluded that the GA algorithm was able to produce the best route effectiveness of 35.5% with a minimum distance of 76.4 km with the route 1-16-7-14-13-17-21-22-6-19-18 - 3-23-9-19-15-24-4-15-20-8-11-2-25-5-2 and a travel time of 4 hours 51 minutes and a fee of Rp. 213,000 with a delivery route on the test.